(untitled) (International Journal of Nursing Education, 2020)
Communication with peers and making decisions are the main successful components in code blue teamactivation. Communication provides information concerning patients. Thus, code blue team activationbecomes the appropriate thing. This research aims to find out the nurses’ communication toward the codeblue team activation decision in the hospital. This research applied a cross-sectional study design. Theapplied sampling technique was purposive sampling. The sample consisted of 93 hospitalized patients. Thedata collection was done by distributing the questionnaire. The questionnaire had undergone validity andreliability tests. The data analysis process applied spearman rank statistics test and multiple linear regression.The results show that the average score of nurses’ communications is 34.7 (SD + 2.23). The decision makingof the nurses was based on their intuition, 72%. The linear regression shows the communication componentin the form of common interest. It became the dominant factor in decision making. It could be concludedthere was communication influence in deciding the code blue team activation.